Ugrupowanie polityczne księcia A. J. Czartoryskiego wobec misji dyplomatycznej lorda J. G. L. Durhama do Petersburga w 1832 r. - Żurawski vel Grajewski, Radosław (Acta Universitatis Lodziensis. Folia Historica, 1998)
Lord John G. L. Durham’s mission to Petersburg (July-October 1832) made an unexpected opportunity for Prince A. J. Czartoryski’s diplomatic activity on Polish matters. Prince Adam met British diplomat and provided him with many memorandums and instructions, concerning goals and ways of negotiations with tsar Nicholas I. He emphasized a necessity for opposing an international agreement on Russian changes in legal status of the Kingdom of Poland, as well as, treatment of Polish issue as a domestic problem of Russia. He tried to win a support for basing future negotiations on Vienna Treaty decisions and for future international conference on Polish matters. He argued for co-operation between France and Great Britain and for similar diplomatic missions to Berlin and Vienna. He also demanded British support for pro-Polish propaganda in Great Britain. Lord J. Durham did not run a risk of talking with tsar about Polish matter and he achieved no serious results concerning that issue. It happened so because an agreement with Russia on Belgian matters was regarded by British government as the most important goal of the mission, as well as, Russians did not tolerate any talks about Poland. Both Lord J. Durham and Prince A. J. Czartoryski considered a war against Russia to be the only possibility for solving Polish matter, and both were aware Britain was unable to decide on it then. In fact, Durham’s mission gave some positive results for Polish matters: Britain unofficially recognized breaking Vienna Congress decisions in Poland, as well as, appreciated importance of Czartoryski’s diplomatic service as a source of information. British press remained mostly anti-Russian.